Evaluation of training methods in an urban agriculture apprenticeship program - Gilmore, Jesse R. (Kansas State University, 2019)
Place-based education is used throughout agricultural education as a means of experiential learning and is a powerful tool for training adult beginning farmers due to its ability to provide context, utility, independence, and use for previous experiences in the learning process. Apprenticeship – one method of place-based learning – is widespread in United States agriculture, particularly in the organic vegetable production sector. Researchers have analyzed the goals of apprenticeship programs and their training methods, but little research exists analyzing the effectiveness of these training methods. Growing Growers is an Extension-partnered apprenticeship program in Kansas City that offers participants sustainable agriculture training in three learning environments: workshops, host farm mentoring, and experiential, employment-based learning. This training and instructional format provides a unique opportunity to analyze the effectiveness of learning environments in an agricultural context. A survey was developed to understand the training methods of the program’s host farms and preferred learning environments of program participants. Following survey distribution, the results were used to identify effective learning environments, and recommendations are made for the improvement of Growing Growers as well as similar programs. Survey results indicated that participants preferred formal environments for four learning objectives, mentoring for two learning objectives, field work for three learning objectives, and had no learning environment preference for five learning objectives. Additionally, participants indicated that nine learning objectives need formal educators, and eight need contextual application. Three learning objectives (production planning, small farm equipment, insect management) require both formal educators and contextual application. Respondents almost unanimously indicated that their business management training was lacking, confirming previous research that mentioned apprenticeship programs’ inability to connect participants to business start-up resources. In particular, participants were not comfortable with land acquisition and capital, which prevented many apprentices from pursuing commercial food production. Recommendations regarding future changes to the program concern business management education, including adding project-based business plan development, providing locations for apprentices to contextually apply business management knowledge, and exploring alternatives to land acquisition.
Keywords: Apprenticeship; Learning environment; Sustainable agriculture; Vocational education; Andragogy; Program development